Strategi pemuda Gang Tato Desa Kemantren Kabupaten Malang melawan stigma sosial - Risdawati Ahmad; Joan Hesti Gita Purwasih; Irawan Irawan (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
This thesis attempts to review how the Young People of Tattoo Alley interpret tattoos and social movements carried out to fight stigma. The process of extracting data is done through a qualitative approach. This study uses data collection techniques such as observation, interviews and documentation. The research location is in Tattoo Alley, Kemantren Village, Malang Regency. The process of data analysis is done through data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, the validity of the data was examined using source triangulation techniques. The results of this study indicate that: First, there are two types of meaning of tattoos that are distinguished by phase, namely the first phase of meaning of tattoos tends to be negative, while the second phase of tattoos is more positively interpreted. Second, forms of social movements undertaken by Tattoo Alley Young People to fight stigma and discrimination include: conducting tutoring, training in mask craft, training in traditional musical instruments, and implementing teaching programs conducted by thugs. DOI: http://dx.doi.org/10.17977/um022v5i22020p63